Contextualising fasad for environmental stewardship: Islamic spirituality and the hierarchy of values in contemporary ecotheology - Sri Hariyati Lestari; M. Zia Al-Ayyubi (Al'Adalah, 2025)
The global ecological crisis represents a fundamental ethical shift, yet Islamic ecotheology often remains at the level of normative affirmation without an operational framework. This study aims to reframe the Qur’anic concept of corruption (fasad) as ecological corruption and map its normative status within contemporary environmental stewardship. Employing Abdullah Saeed’s contextualist hermeneutics and the hierarchy of values framework, the research adopts a normative-analytical design to derive a measurable logic of responsibility. The study finds that by situating the prohibition of fasad as a universal protection value, environmental stewardship transcends optional virtue to become a mandatory legal-ethical parameter. This classification allows for a rigorous distinction between substantive ecological reform and destructive pseudo-reform often found in developmental rhetoric. Furthermore, the research integrates ecospirituality as an infrastructure of meaning to ensure the internal consistency of pro-environmental behaviour. By synthesising fasad protective boundary, the khalifah mandate, and hifdz al-bi’ah of maqasid al-shariah, this study offers a disciplined moral architecture for public policy. This study provides a methodological foundation for translating sacred texts into adaptive governance instruments that address intergenerational justice and systemic ecological integrity.